DETERMINAN PENGHINDARAN PAJAK: LIKUIDITAS, LEVERAGE, AKTIVITAS, PROFITABILITAS, PERTUMBUHAN DAN NILAI PERUSAHAAN - Arswendy Danardhito; Hendro Widjanarko; Heru Kristanto (JURNAL PAJAK INDONESIA, 2023)
This research analyzes the effect of various financial ratios on tax avoidance. The ratios are liquidity, leverage, activity, profitability, growth and firm value ratio. Population in this research are all of go public company listed in the Indonesia Stock Exchange (IDX) of the year 2016-2020. The purposive sampling method was used to select sample of this research which consists of 84 companies during 5 years with the result that the total sample (n) was of 410 data. The research hypothesis testing uses multiple regression analysis techniques using SPPS 26. This study concludes that profitability has a positive effect on tax avoidance, while firm value has a negative effect on tax avoidance. Liquidity, leverage, activity and growth have no effect on tax avoidance. Profitability has the most dominant influence on tax avoidance compared to other variables.